Tracing Teutonic footprints in VET around the world?. Issue 8 (27th August 2014) - Pilz, Matthias; Li, Junmin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to focus on the vocational and training behaviours of German corporations at their subsidiaries in the USA, China and India. Although all three countries are important markets for Germany, they are characterised by very different cultures, vocational education and training (VET) systems and employment systems. The transfer of the German VET system to other countries has been the topic of discussion and controversy. Design/methodology/approach – In this study, the authors rely on interviews with local training experts of German subsidiaries to analyse VET activities. Their analysis is based on convergence (standardisation) versus divergence (localisation) theory borrowed from approaches in international management studies. Findings – The findings indicate a "localisation" effect in all three nations. The similarities can be explained partially by the stronger focus on off-the-job trainings and greater preferences for academic careers. Research limitations/implications – The study is a pilot study. Practical implications – The transfer of the German VET system to other countries seems to be very difficult. Originality/value – Beyond this general debate, the specialist literature pays virtually no attention to the training practices of German companies abroad. The authors have tried to fill this research gap.